1997
DOI: 10.1002/zaac.199762301131
|View full text |Cite
|
Sign up to set email alerts
|

Die Kristallstrukturen von CsBiO2 und Cs3BiO3

Abstract: CsBiO2 (hellgelb) und Cs3BiO3 (gelb) wurden durch Festkörperreaktion aus den binären Komponenten Cs2O und Bi2O3 bei Temperaturen von 700°C bzw. 550°C dargestellt. In CsBiO2 liegen nach der Einkristallröntgenstrukturanalyse (C2/c; a = 827,4(2); b = 920,4(2); c = 597,87(9) pm; β = 122,51(1)°; Z = 4; 975 Diffraktometerdaten; R1 = 0,058; wR2 = 0,077) unendlich ausgedehnte  ∞1[BiO2/2O′2/2]‐Ketten vor. Die Kristallstruktur von Cs3BiO3 (P213; a = 920,86(8) pm; Z = 4; 289 Diffraktometerdaten; R1 = 0,048; wR2 = 0,081) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…(14)(15)(16)(17)(18). From atomic positions given in the literature, the locations of the lone pairs of the bismuth atoms have been determined by using the calculation method described above in Section 2 and the oxygen environments of Bi are discussed.…”
Section: Simple Bismuth Oxidesmentioning
confidence: 99%
“…(14)(15)(16)(17)(18). From atomic positions given in the literature, the locations of the lone pairs of the bismuth atoms have been determined by using the calculation method described above in Section 2 and the oxygen environments of Bi are discussed.…”
Section: Simple Bismuth Oxidesmentioning
confidence: 99%
“…structure of elemental calcium (O'Keeffe & Hyde, 1985) and that the three O atoms of some ABO 3 perovskites are inserted into the holes of the corresponding AB alloys without any volume increase (Martõ Ânez-Cruz et al, 1994;RamosGallardo & Vegas, 1997). Other compounds which behave in this manner are the tetragonal YbOOH (Vegas & Isea, 1997) and Cs 3 BiO 3 (Zoche & Jansen, 1997).…”
Section: The Rare Earth Dioxidesmentioning
confidence: 99%
“…We have reinvestigated the compounds ABiO (A"K, Rb, Cs), revised the former crystal structure determinations, and found that all compounds from sodium to caesium are isostructural (5,6). In the A BiO series we found K BiO (7), which has the same crystal structure as Na BiO .…”
Section: Alkali Metal Oxobismuthates(iii) Abiomentioning
confidence: 89%